SOSIALISASI BAHAYA BORAKS DAN FORMALIN PADA MAKANAN DI SMPN 3 TEBAS: Socialization Of The Danger Of Borax And Formalin In Food At SMPN 3 Tebas - Gusti Randy Pratama; Kiki Kristiandi; Ruwendi Alfaisyal; Nurul Pratiwi; Puspa Puspa; Era Sabrina; Indah Indah; Ismiadi Ismiadi (Pakis Journal Institute, 2023)
Borax and formalin are chemicals that are prohibited by law as food additives. Borax and formalin contain preservatives that are harmful to the body. There are many uses of borax and formalin in processed food circulating in the community so students must be more careful in choosing healthy foods. This socialization aims to increase students’ knowledge about the dangers of borax and formaldehyde and to be more careful in choosing food. The activity was carried out at Tebas 3 Public Middle School, on Wednesday, June 7, 2023. The socialization method used in this activity focused on communication, information, and education activities. The result of this socialization is that students become more careful in choosing nutritious foods and know the characteristics of foods that contain borax and formalin. Tebas 3 Public Middle School students who are in their teens need a balanced nutritional intake and must consume healthy and nutritious food so that the socialization of the dangers of borax and formalin can increase the knowledge, concern, and understanding of these students